Kwaito Bodies: Remastering Space and Subjectivity in Post-Apartheid South Africa. Xavier Livorman, 2020. Durham: Duke University Press. 35 illustrations b&w, glossary, bibliography, index, 288pp. - de Vries, Lee-Ann (International Library of African Music, 2022)
pages: 127-129
Keywords: South Africa; Kwaito (Music); African Music